2022
DOI: 10.3390/ijerph19052794
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Psychological Vulnerability in First Responders: Monitoring Depersonalization and Phobic Anxiety during the COVID-19 Pandemic

Abstract: Background: It is common knowledge that first responders are among the helping professionals most at risk of burnout and psychological vulnerability. During the COVID-19 pandemic, their mental health has been subjected to various risk factors. Methods: Data on socio-demographic characteristics, the Maslach Burnout Inventory (MBI) and psychological vulnerability (SCL-90-R) were obtained from 228 subjects (55.3% female; M age = 45.23, SD = 13.14) grouped on the basis of their actual involvement during the emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The results of this study addressing the relationship between job satisfaction and burnout are in line with the findings of a study by Oliveira et al [ 46 ], in which the absence of burnout was identified as a predictor of job satisfaction. As for the relationship between psychological vulnerability and burnout, Benincasa et al [ 47 ] also advocated that lingering chronic psychological vulnerabilities can lead to the exhaustion of personal resources, favouring the onset or prevalence of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study addressing the relationship between job satisfaction and burnout are in line with the findings of a study by Oliveira et al [ 46 ], in which the absence of burnout was identified as a predictor of job satisfaction. As for the relationship between psychological vulnerability and burnout, Benincasa et al [ 47 ] also advocated that lingering chronic psychological vulnerabilities can lead to the exhaustion of personal resources, favouring the onset or prevalence of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests a significant negative impact of the pandemic on employees in healthcare and frontline medical positions (Baskin & Bartlett, 2021). Studies from diverse academic fields such as psychology, sociology, and social work have demonstrated impacts on frontline medical workers’ levels of stress (Goh et al, 2020; Lorente et al, 2020; Luceño-Moreno et al, 2020), burnout (Hu et al, 2020), anxiety (Barzilay et al, 2020; Benincasa et al, 2022; Lapum et al, 2020), and resilience (Jose et al, 2020; Labrague & Santos, 2020; Pink et al, 2021). Notably, there is still much unknown about how the COVID-19 pandemic or public health crises, in general, exacerbate work-related consequences among firefighters, law enforcement, and emergency medical workers comparatively and collectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the work of first responders is often fulfilling to individuals who have chosen to enter the profession, there are well-documented risks and consequences of the job (Benincasa et al, 2022). First responders regularly witness death, illness, injury, and destruction and are tasked with saving lives and preserving property during emergencies.…”
Section: Work-related Risks and Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such disorders present with a variety of symptoms, including stress, depression, anger, fatigue, insomnia, substance abuse, and increased suicidality ( 3 , 4 ). Available evidence suggests that particular professions have an increased risk for symptoms of mental health disorders, including first responders ( 5 ), medical professionals ( 6 ), and members of the armed forces. Within the latter, the literature increasingly supports a Consequence of War Syndrome (CWS) to describe a cluster of symptoms experienced by members of the armed forces including chronic pain, insomnia, and other physical complaints along with PTSD, anxiety, depression, anger, and neuropsychological deficits ( 7 ).…”
Section: Introductionmentioning
confidence: 99%